PENINGKATAN KOMPOTENSI GURU AGAMA HINDU MELALUI PEMBINAAN OBSERVASI KELAS DI GUGUS 2 KINTAMANI KABUPATEN BANGLI SEMESTER GANJIL TAHUN PELAJARAN 2018/2019 - I Wayan Suardana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
The aims of this study is to improve the competence of Hinduism teachers at the elementary level in 2nd Group of Kintamani district, and in Bangli Regency. This study is a Regional School Action Research (PTSW) using three cycles design and each cycle consists of four stages, namely: planning, action, observation, and reflection. A measurement technique in the form of test is used to carry out the teaching and learning process. Then, an observation in teaching and learning process are used to collected a quantitative data and it presented in the form of qualitative data. Furthermore, based on the results of this study, it can be found that; first, at the end of the first and second cycles there was an increase in the average results of teacher's potential through training in making lesson plan of 2013 Curriculum from 76.00 to 85.60 after the second and third cycles at the professional level the teacher achieved good grades. Second, it turned out that the increase in teacher's Compensation through classroom observation guidance in the 2nd group in Kintamani and in Bangli regency 2018/2019 showed very significant results from the initial conditions before receiving training. It turns out that teacher training through classroom observation is very useful to increase teacher's potential. However, they can increase their confidence in carrying learning tasks.